AKSI KEMANUSIAAN DALAM BINGKAI POLITIK - Sofjan, Noorwahid (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi; Vol 15 No 1 (2019), 2020)
Discourse about human rights (human rights talk) can not be separated from the discussion of philosophy, law, and politics. In the meantime, to build a comprehensive understanding of human rights and their relationship with politics and humanitarian action, this paper will provide a brief overview of the history of human rights. Then a review of human rights based on the three levels of analysis above. In the philosophical aspect, will be reviewed regarding the development of the idea of human rights. Followed by a discussion of the legal nature of the law and its relationship to the normative ideal values that underlie humanitarian action. And finally, the discussion is about the political dynamics that characterize the issue of human rights and humanitarian actions.